Loss of long-term non-progressor and HIV controller status over time in the French Hospital Database on HIV - ANRS CO4 - Grabar, Sophie; Selinger-Leneman, Hana; Abgrall, Sophie; Pialoux, Gilles; Weiss, Laurence; Costagliola, Dominique (PloS one, 2017)
We studied the frequency and risk factors for loss of long-term non-progressor (LTNP) and HIV controller (HIC) status among patients identified as such in 2005 in the French Hospital Database on HIV (FHDH-ANRS CO4). We selected patients who were treatment-naïve and asymptomatic in 2005 (baseline). Those with ≥8 years of known HIV infection and a CD4 cell nadir ≥500/mm3 were classified as LTNP and those with ≥10 years of known HIV infection and 90% of plasma viral load (VL) values ≤500 copies/ml in the absence of cART as HIC. cART initiation without loss of status and death from non AIDS-defining causes were considered as competing events. After 5 years of follow-up, 33% (95%CI; 27-42) of 171 LTNP patients and 17% (95%CI; 10-30) of 72 HIC patients had lost their status. In multivariable analyses, loss of LTNP status was associated with lower baseline CD4 cell counts and CD4/CD8 ratios. Only VL was significantly associated with loss of HIC status after adjustment for the baseline CD4 cell count, the CD4/CD8 ratio, and concomitant LTNP status. The hazard ratio for loss of HIC status was 5.5 (95%CI, 1.5-20.1) for baseline VL 50-500 vs ≤50 cp/mL, after adjustment for the baseline CD4 cell count. One-third of LTNP and one-fifth of HIC patients lost their status after 5 years of follow-up, raising questions as to the possible benefits and timing of ART initiation in these populations.